2011
DOI: 10.1038/ajh.2010.214
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Red Wine on Adipocytokine Expression and Vascular Alterations in Fructose-Fed Rats

Abstract: In this study, Malbec RW, but not alcohol alone, improved the balance of adipocytokines and attenuated the oxidative stress and vascular inflammation in a model of MS, suggesting that nonalcohol components of RW are responsible for the beneficial effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 40 publications
2
28
0
Order By: Relevance
“…Several studies have shown that adipose tissue contributes to the modulation of changes in a variety of bioactive adipocytokines, such as adiponectin, leptin, visfatin, and resistin, leading to vascular injury and target organ damage [38, 39]. In the current study, the high-fructose diet significantly reduced serum adiponectin levels and increased serum leptin, resistin, and visfatin levels by increasing adipose Ang II expression.…”
Section: Discussionsupporting
confidence: 48%
“…Several studies have shown that adipose tissue contributes to the modulation of changes in a variety of bioactive adipocytokines, such as adiponectin, leptin, visfatin, and resistin, leading to vascular injury and target organ damage [38, 39]. In the current study, the high-fructose diet significantly reduced serum adiponectin levels and increased serum leptin, resistin, and visfatin levels by increasing adipose Ang II expression.…”
Section: Discussionsupporting
confidence: 48%
“…While promoting the expression of adiponectin, a fat-derived adipokine that exerts powerful anti-inflammatory effects, ethanol or wine ingestion also reduced the release of inflammatory cytokines and pro-inflammatory mediators from human adipose tissue under basal conditions and following exposure to lipopolysaccharides [13,212,213]. …”
Section: Ethanol Exerts Anti-inflammatory Effects In I/r: Cellularmentioning
confidence: 99%
“…The mass of abdominal fat expressed as a percentage of the body weight has been previously used as a measure of body composition in rats (16). No statistically significant change was observed in this percentage due to PTU (11.3±1%) or T 4 (9.1±0.6%) treatments compared with controls (11.5±0.7%), although the HyperT rats had a tendency to show lower values.…”
Section: Induction Of Hypothyroidism and Hyperthyroidismmentioning
confidence: 72%